A pendulum-based absorber-harvester with an embedded hybrid vibro-impact electromagnetic-dielectric generator. (March 2023) - Zhang, Cailiang; Xu, Junchen; Fang, Shitong; Qiao, Zijian; Yurchenko, Daniil; Lai, Zhihui
Abstract: In this paper, a novel hybrid vibro-impact electromagnetic-dielectric generator (VI EDG) is proposed, which is further embedded into a pendulum structure to form a pendulum-based absorber-harvester (PAH) system. The PAH system can convert the vibration energy into electrical one with the help of the VI EDG, and has the potential to reduce the swing amplitude of the pendulum. The physical model of the PAH system is first introduced, and its governing equations involving the dynamical and electrical parts are derived based on the Euler-Lagrange's equation of a non-conservative system. Next, the governing equations of the PAH system are validated experimentally by measuring the swing motion of the pendulum under a given harmonic excitation. On this basis, the system energy harvesting performance under different excitation parameters (amplitude and frequency) and dimensional parameters (the rod's length and the distance between two dielectric elastomer membranes) is fully investigated and explained through numerical simulations. Finally, the vibration absorption performance of the VI EDG is discussed by comparing the peak-to-peak values of the swing motions between the proposed PAH system and the conventional pendulum without embedded VI EDG. Research results show that the proposed VI EDG can not only effectively harvest ambient vibration energy from the pendulum system, but also has the potential to absorb the vibration of the system. Graphical Abstract: ga1 Highlights: A VI EDG embedded in PAH is proposed for energy harvesting and vibration absorption. The governing equations of the PAH system with embedded VI EDG are derived. The highest output power of 8.697 mW is achieved from the PAH system. The highest energy conversion efficiency of 21.83% is achieved from the PAH system. The VI EDG can reduce the swing amplitude of the PAH system as much as 24.32%.